Gestión administrativa en la empresa constructora Chalett S.A. - Viteri Velez, Jorge Washington (2019)
The company Constructora Chalett S.A. Cochaletsa is dedicated to the construction of civil works for: power plants, power transmission lines and communications; Auxiliary works in urban areas, it is located in the streets 5 de Junio and Roldós, in the villas of the Ecuadorian Housing Bank, currently has a manager, an accounting assistant, a winemaker, resident of works and the workers who are dedicated to the construction The problem in this case study is the difficulty in its administrative management, which is generated due to the lack of an economic budget, lack of plant employees and a deteriorated corporate image, this has caused the company to not be well positioned in the community, resulting in low income and danger of stability; without action plans to overcome them have been undertaken to date. The sub-line of applied research is: Administrative Management Model, precisely because of the administrative problems presented by the company; In conclusion, it was determined that the administrative management of the company is in a decline due to the form of work that is being carried out and that the lack of economic capital for the acquisition of inventories has caused that the delivery deadlines of the companies are not met. works; The corporate image of the company is impaired, and the way of working in reference to the economic management of resources is not adequate